Peran Lembaga Bantuan Hukum Dalam Meningkatkan Akses Keadilan Bagi Masyarakat Miskin di Indonesia - Hadri, Hadri (Muhammadiyah Law Review Journal, 2025)
Humans have the right to justice, including poor people who have difficulty obtaining legal services. The Legal Aid Institute (LBH) played a role. Contribution in ensuring that underprivileged communities receive fair legal protection through free legal assistance, policy advocacy and legal education. However, LBH faces many challenges, such as lack of funding, lack of human resources, and geographic barriers that prevent people in remote areas from obtaining legal services. According to an analysis of LBH's performance in Indonesia, the success of legal aid is highly dependent on government policy support, cooperation with non-government organizations, and increasing public legal awareness. Legal aid services in Indonesia face problems in funding coverage and sustainability, compared with the system in the United States. In the United States, the Public Defender system ensures that defendants in criminal cases can have an attorney, and more law firms offer pro bono services. Strategic steps, such as increasing funding, utilizing online consultation legal education technology, and strengthening the role of paralegals in helping communities in remote areas, are needed to increase LBH's role in increasing access to justice for poor communities in Indonesia. With better cooperation between government, the private sector, community organizations and academia